Xerosis cutis in patient with chronic renal failure - Putri S, Desy Sahara; Dalimunthe, Dina Arwina (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Chronic kidney disease (CKD) is a multifaceted condition that affects multiple organs including the skin. Xerosis is the most prevalent skin manifestation in CKD.Objectives: This study aimed to present clinical findings that can assist healthcare professionals in diagnosing and managing common skin conditions, particularly xerosis, which frequently occurs in patients with Chronic Kidney Disease (CKD).Methods: This study used a descriptive method with a case study approach. The case description is A 31-year-old-man consulted our department with dry, scaly, and itchy skin throughout his body for 5 months. Initially, the patient felt itchy throughout the body, and the skin felt dry and spread throughout the body. He was also diagnosed with chronic kidney disease with an eGFR value of 5.81 mL/min/1.73 m2. Dermatological examination showed xerosis with fine scales, hyperpigmented macules, multiple, well-defined, lenticular-plaque size in the fascial, anterior and posterior thoracic,wasominal, bilateral brachial, bilateral antebrachial,and  bilateral anterior and posterior femoral, bisizesral anterior and posterior cruris regions.Results: Laboratory results revealed a urea level of 199 mg/dL and a creatinine level of 8.0 mg/dL. The patient was diagnosed with xerosis cutis and underwent multidisciplinary assessment involving dermatology and internal medicine. Conclusion: The diagnosis in this patient was made clinically based on history, physical examination, and laboratory tests. Early diagnosis of xerosis can improve quality of life and reduce skin manifestations.